TRANSFORMASI STRATEGI PEMASARAN: INTEGRASI DIGITAL MARKETING DENGAN ANALITIK PREDIKTIF - Rachim, Silfia; Maryati, Sri; Yudhatama, Yoram; Rohendi, A. (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2025)
The advancement of digital technology has transformed the marketing landscape, encouraging organizations to adopt adaptive, data-driven strategies. Digital marketing today not only enhances visibility and consumer interaction but also leverages predictive analytics to forecast behavior, preferences, and market trends. This article analyzes the transformation of marketing strategies through the integration of digital marketing and predictive analytics, as well as its implications for campaign effectiveness and business decision-making. The study employs a literature review approach, drawing on recent sources from accredited international and national journals. Findings indicate that predictive analytics improves market segmentation accuracy, content personalization, and promotional budget efficiency. This integration enables proactive, evidence-based marketing strategies that strengthen organizational competitiveness. Practical recommendations include strengthening data infrastructure, enhancing human resource analytical competencies, and fostering cross-functional collaboration.